Pembelajaran Pendidikan Agama Islam berdasarkan pendekatan logis untuk meningkatkan pikiran kritis dan motivasi berprestasi di SMK Kita Bhakti dan SMK Raden Fatah Mojosari - Syu'aib Nawawi (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Science given by God to man through his brain an integral part of the values of divinity as essential sources of knowledge, is of God. Apart from the paradigm that reduces intuition and metaphysical things, al-Qur'an as unceasingly called for people to continue reviewing, researching, studying, thinking and examine all of the phenomena that exist, because nothing in this world that is created in vain. The motivation given, is nothing for man to know and realize the power of his mind in order to add to the faith in God. Fortunately models such as the way of thinking so that the characteristics of 2013. The curriculum is a danger that a scientific approach that uses the methods of scientific thinking stands by itself without any control limit values contained wise in religion (Islam). Make learning Islamic education students based on a logical approach to improve critical thinking and motivation of achievement in SMK and SMK Bhakti We Raden Patah Mojosari be an interesting learning model and help teachers to improve learning effectiveness. This study used a qualitative approach through case studies. Researchers conducted this study to determine "how" (how) Implementation of Islamic religious education teaching third grade students based on a logical approach to improve critical thinking and motivation of achievement in SMK and SMK Bhakti We Mojosari Raden Patah. This study tends toward descriptive because its purpose is to describe and analyze the data obtained in depth with the hope to find out in detail the implementation of Islamic religious education third grade student learning based on a logical approach to improve critical thinking and motivation of achievement at SMK We Bhakti and vocational Raden Patah Mojosari. From in-depth analysis can be summarized as follows: 1) We approach learning in SMK and SMK Bhakti Raden Patah Mojosari logical approach emphasizes the processes and skills in accordance with the learning materials. materials adapted to the level of development of learners learn. 2) Implementation of the learning curriculum implemented in 2013 at SMK and SMK Bhakti We Raden Patah Mojosari using a scientific approach. The learning process touches three domains, namely the attitude, knowledge and skills. 3) Questions or both written and oral evaluation of teaching is based on a logical approach to improve critical thinking and motivation of achievement in SMK and SMK Bhakti We Raden Patah Mojosari good and inspire learners to give a good answer and true anyway. 4) Study of Islamic education is based on a logical approach becomes more meaningful and real. This means that students are required to be able to capture the relationship between the experience of learning in school to real life. However, in this context, of course, teachers need extra attention and guidance to students so that learning objectives in accordance with what was originally applied